The purposes and validity of vocational qualifications - Stasz, C (ESRC Centre on Skills, Knowledge and Organisational Performance (SKOPE), 2011)
UK policy makers continue to focus on increasing skills as a means to economic and social prosperity and social mobility. Qualifications - the certificates and diplomas awarded following education, training or learning - stand as a proxy for skill and many policies aim to raise levels of qualifications held. Policy makers have focused much attention on vocational qualifications and history is replete with efforts to reform the vocational education and training (VET) system. Many studies have identified both strengths and weaknesses in the current system, most recently the Wolf Review (2011). This paper does not attempt to cover old ground, but to look at more basic questions: What are the purposes of vocational qualifications? Are they fit for those purposes? While the first question has been addressed in policy and scholarly circles, less attention has been paid to the second question. This paper draws on literature related to the validity of assessment, because an award of vocational qualification rests on a candidate's successful performance on particular types of assessment tasks. It examines conceptions of validity and their implications for the interpretation of assessment results. The review shows that judging the validity of vocational qualifications is much more complicated than the architects of National Vocational Qualifications envisaged. The purposes of vocational qualifications have expanded and also vary for different stakeholders. The paper argues that the extent to which vocational qualifications support valid inferences for different purposes remains largely unexplored.